The Development of the Service System of Premium Heart Health Clinic at Queen Sirikit Heart Center of the Northeast, Thailand - Dapha, Sompratthana; Srijakkot, Jitpinan; Sookpier, Pornpimol; Jantachum, Wanchanok; Makarawate, Pattarapong; Saensaeng, Benchamat; Duangdeun, Saranya; Chaipeerawat, Kanpaweesoo; Buakaew, Warunporn (South Eastern European Journal of Public Health, 2024)
Background: Developing a quality service system is a challenge in the health system amidst resource constraints and increasing service recipient expectations. This action research developed the service system of Premium Heart Health Clinic at Queen Sirikit Heart Center of the Northeast, Thailand, and evaluated the outcomes of the service delivery duration and the satisfaction with services. Method: The action research framework was employed. The study process comprised the following four steps: 1) analyzing the situation, 2) designing and developing the service system, 3) trying out the service system and 4) evaluating the service system. The research tools were the service duration record form and the service recipient satisfaction assessment form. Data were analyzed by descriptive statistics, including frequency, percentage, mean, and standard deviation, and independent t-test and content analysis. The findings revealed that the developed service system of Premium Heart Health Clinic at Queen Sirikit Heart Center of the Northeast, Thailand was the TPCG model, comprising 4 elements: Teamwork (T), Preparation of service provider competencies (P), Creating a marketing plan (C) and Growth mindset (G). It was also found that the mean service duration at Premium Heart Health Clinic after the development of the service system was significantly lower than that of before the development (p< 0.01) (before: 138.09; after: 222.42). The mean satisfaction was also significantly higher than before the development (p< 0.01) (before: 3.74; after: 3.52).